Pulsating flow in a planar diffuser upstream of automotive catalyst monoliths - Mat Yamin, Ahmad Kamal; Benjamin, Stephen; Roberts, Carol A. (ELSEVIER, 2013)
The flow distribution across automotive exhaust catalysts has a significant effect on their conversion efficiency. The exhaust gas is pulsating and flow distribution is a function of engine operating condition, namely speed (frequency) and load (flow rate). This study reports on flow measurements made across catalyst monoliths placed downstream of a wide-angled planar diffuser presented with pulsating flow. Cycle-resolved particle image velocimetry (PIV) measurements were made in the diffuser and hot wire anemometry (HWA) downstream of the monoliths. The ratio of pulse period to residence time within the diffuser (defined as the J factor) characterises the flow distribution. During acceleration the flow remained attached to the diffuser walls for some distance before separating near the diffuser inlet later in the cycle. Two cases with J ∼ 3.5 resulted in very similar flow fields with the flow able to reattach downstream of the separation bubbles. With J = 6.8 separation occurred earlier with the flow field resembling, at the time of deceleration, the steady flow field. Increasing J from 3.5 to 6.8 resulted in greater flow maldistribution within the monoliths; steady flow producing the highest maldistribution in all cases for the same Re.